IPA FONDOVI CBC- MOGUĆNOST ZA RAZVOJ TURIZAMA - Maksimović, Aleksandar; Todorović, Ljubiša; Ćejvanović, Ferhat (Economics of Agriculture, 2011)
The European Union in different ways and through the structural funds, helps developing countries in the Western Balkans. Decision of the EU, the total amount that will in the period since 2007. 2013. be available in Turkey, Croatia, Serbia, Macedonia, Albania and Bosnia and Herzegovina is 4 billion. One of the priority measures under the IPA Cros-border coopertion (CBC) is the development of tourism. These measures should help the development of tourism. How and how to access and become a user of these programs help? Cross-border projects, involves regional cooperation, and require fnancial resources in the preparation of the project. Trained project manager are needed for this job. Local communities, with its capacity should take on the preparation of these projects, as partners include the tourist industry and animate other tourist facilities in their local community.